Evaluation of Indonesian language course development focused on internationalization with goal-oriented model - Etika Rahmawati, Laili; Sulistyono , Yunus; Ratih, Koesoemo; Hamidah, Jamiatul; Istiqamah, Istiqamah; Utami , Nindy Muji; Ariyanto , Zahy Riswahyudha; Fadilla, Maya Ratu; Noviafitri, Kartika Satya (Universitas Ahmad Dahlan, 2024)
Currently, the gap between the theory taught in lectures and the practical needs in Indonesian language internationalization projects hinders students' mastery of competencies in studying the Indonesian Language Development course. There is a pressing need to update the Indonesian Language Development curriculum to emphasize practical application, such as language development projects and the use of Indonesian in international contexts. Active student involvement through participatory and collaborative approaches is key to preparing students for the challenges of Indonesian language development in the era of globalization. This study aims to evaluate the Indonesian Language Development course, focusing on the internationalization of the language, and is based on participatory and collaborative learning. The method employed is the Goal-Oriented Evaluation Model, which involves identifying specific needs by analyzing issues in the Indonesian Language Development course. It identifies the objectives of the internationalization program based on clear indicators and proposes actions to improve teaching and learning. Data collection methods include classroom observations, student performance surveys, and interviews, along with a literature review to support an understanding of suitable participatory and collaborative learning methods The findings show that teaching methods incorporating technology, field practice, and interactive activities create positive and meaningful learning experiences. The evaluation, including student participation and collaboration, has yielded favorable results, with most respondents reporting that this learning is enjoyable, beneficial, and memorable. In conclusion, the study concludes that the learning approaches at University A and University B are appropriate and effective.